2012
DOI: 10.1007/s00268-012-1809-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Hypoparathyroidism Following Total Thyroidectomy for Thyroid Cancer

Abstract: Careful surgical technique for in situ preservation of parathyroid gland and autotransplantation of inadvertently removed parathyroid gland are important, especially in case of gross extrathyroidal extension. Adequate surgical experience is also an important factor. And routine bilateral central lymph node dissection should be done thoughtfully for its effect on postoperative hypoparathyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
91
0
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 37 publications
4
91
0
13
Order By: Relevance
“…These cases account for all the procedures of the neck region that resulted in impaired parathyroid function and involved a mean of 1.3/100,000 inhabitants per year during the observation. Overall, the prevalence of postsurgical hypoparathyroidism in previous reports varied according to centers of different expertise and experience [1][2][3][4][5][9][10][11][12][13][14]. The type and extension of surgery of the neck structures and, consequently, the underlying disease, as well as repeated surgeries, can also affect the rate of postoperative hypoparathyroidism [1,11,15].…”
Section: Discussionmentioning
confidence: 99%
“…These cases account for all the procedures of the neck region that resulted in impaired parathyroid function and involved a mean of 1.3/100,000 inhabitants per year during the observation. Overall, the prevalence of postsurgical hypoparathyroidism in previous reports varied according to centers of different expertise and experience [1][2][3][4][5][9][10][11][12][13][14]. The type and extension of surgery of the neck structures and, consequently, the underlying disease, as well as repeated surgeries, can also affect the rate of postoperative hypoparathyroidism [1,11,15].…”
Section: Discussionmentioning
confidence: 99%
“…Preservation of parathyroid in situ is more physiologically natural, but it is often technically difficult. Paek et al demonstrated that surgeon's skill is an independent risk factor of permanent hypoparathyroidism on multivariate analysis [20]. Only one surgeon (Akira Miyauchi) performed surgery for the series of patients of Kihara et al [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of HPT is inadvertent damage or removal of the parathyroid glands during thyroidectomy [6,8,19,20]. After total thyroidectomy, transient HPT can be observed in as high as 10% of patients.…”
Section: Discussionmentioning
confidence: 99%